Scientific Research Trends of Flooding Stress in Plant Science and Agriculture Subject Areas (1962-2021) - Nurrahma, Arinal Haq Izzawati; Putri, Hana Haruna; Syahadat, Ray March (Universitas Pendidikan Indonesia (UPI), 2023)
Data collection was gathered from PubMed, Google Scholar, Semantic Scholar, and Crossref in Harzing”s Publish or Perish software. The keyword used in this study was